2020
DOI: 10.3390/foods9091141
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Antibiotic Resistance Profile, Genetic Heterogeneity and Biofilm Production of Methicillin-Resistant Staphylococcus aureus (MRSA) Isolated from The Italian Swine Production Chain

Abstract: The main aim of the present study was to evaluate the level of antibiotic resistance, prevalence and virulence features of methicillin-resistant Staphylococcus aureus (MRSA) isolated from heavy swine at abattoir level and farming environments in Lombardy (Northern Italy). With this scope, 88 different heavy swine farms were surveyed, obtaining a total of n = 440 animal swabs and n = 150 environmental swabs. A total of n = 87 MRSA isolates were obtained, with an overall MRSA incidence of 17.50% (n = 77) among a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 78 publications
3
19
1
Order By: Relevance
“…In this report, the same methodology was utilized (plate-based quantitative measurements), and spa-typing was also performed: overall, isolates belonging to the ST398/t899 and ST398/t011 were the most common among biofilm-producers. 63 El-Nagdy et al detected biofilm-forming S. aureus (using the CRA plate method, complemented with scanning and transmission electron microscopy) from febrile neutropenic patients in Egypt; interestingly, they have found that 72.7% of isolates were biofilm-positive. Among the tested strains, 37.5% were positive for icaA , and 22.9% were positive for icaD ; however, only 50% of biofilm-producers carried either the icaA or icaD genes.…”
Section: Discussion and Review Of The Literaturementioning
confidence: 99%
“…In this report, the same methodology was utilized (plate-based quantitative measurements), and spa-typing was also performed: overall, isolates belonging to the ST398/t899 and ST398/t011 were the most common among biofilm-producers. 63 El-Nagdy et al detected biofilm-forming S. aureus (using the CRA plate method, complemented with scanning and transmission electron microscopy) from febrile neutropenic patients in Egypt; interestingly, they have found that 72.7% of isolates were biofilm-positive. Among the tested strains, 37.5% were positive for icaA , and 22.9% were positive for icaD ; however, only 50% of biofilm-producers carried either the icaA or icaD genes.…”
Section: Discussion and Review Of The Literaturementioning
confidence: 99%
“…The detection of only one MRSA positive sample out of almost 200 tested animals was unexpected. Indeed, the prevalence of MRSA in finishing pigs in another region of northern Italy, Lombardy, was recently estimated at 17.5% [25]. Furthermore, in the south of Italy, prevalences higher than 45% were reported, with the majority of positive samples from intensively reared animals [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Data from one S. aureus strain belonging to t4474 isolated in Switzerland were submitted to a Ridom Spa Server database. Ho et al published a study concerning MRSA from slaughtered pigs sampled from local markets in Hong Kong in 2012 [ 53 ], and Rodríguez-López et al characterized MRSA from the Italian heavy swine production chain in 2020 [ 54 ]. Therefore, the worldwide distribution of this particular spa type is not exactly known.…”
Section: Discussionmentioning
confidence: 99%